The Influence of Work Ethics and Commitment of the Principal on the Visionary Leadership at Junior High School - Ijayani Ijayani; Sumarno Sumarno; Putri Yuanita; Daeng Ayub Natuna; Yoyok Pujianto (STAI Hubbulwathan Duri, 2023)
This study aimed to determine the effect of the work ethic and commitment of the principal on the visionary leadership of Junior High School principals in Pekanbaru City. This study was ex post facto research and used a quantitative approach. The population in this study was composed of 151 principals of junior high schools in Pekanbaru City. The research samples were 110 headmasters of a junior high school in the city of Pekanbaru. The technique used to determine the sample was the cluster sampling method. The data analysis technique used was descriptive statistical analysis and inferential statistical, which consists of F test, Multiple Regression Test, and Determinant test analysis using the SPSS (Statistical Package for Social Science) Version.23 program. The results of the study show that the principal's work ethic and commitment affect the principal's visionary leadership. This means that the better the work ethic and commitment of the principal, the better the visionary leadership of the principal in developing the school. Good visionary leadership can be seen from the leader's insight, the leader's ability to make changes and make decisions, establish good relationships, be innovative and adhere to spiritual values. The principal is a visionary leader to advance the school as shown by his attitude in carrying out work and his concern for the progress of the school.